007 OP: DEVELOPING AND IMPLEMENTING A PERSONAL OUTCOMES APPROACH THROUGH COLLABORATIVE ACTION RESEARCH. (3rd March 2017) - Miller, E; Barrie, K
Abstract : This paper reports on a ten year programme of collaborative action research supporting the development and implementation of a personal outcomes approach in health and social care, culminating in the recent Economic and Social Research Council (ESRC) funded 'Meaningful and Measurable' project. The research brought together academic researchers with practice partners from statutory adult health and social care services, children and families, and third sector carer and mental health organisations. Our primary focus has been working together to find ways to make best use of routinely collected outcomes data, recorded for each service user in the form of a proportionate narrative, to inform individual and collective decision making. Our methodology combined local action research projects in diverse settings with a series of audio-recorded dialogic 'data retreats' for all partners, and knowledge exchange events with wider stakeholders, including commissioning and regulatory bodies. Alongside this, a series of focused workshops were co-created and delivered in response to emergent practice needs, addressing issues including having outcomes focused conversations, outcomes recording practices and pragmatic approaches to qualitative outcomes data analysis and reporting. This paper focuses on the 'how' questions, examining the collaborative mechanisms that proved critical in: 'lifting the rock' to expose hidden assumptions and challenges, including conceptual ambiguities and the subtle yet pervasive nature of positivist influences; learning from local and sectoral differences in establishing the value of different forms of knowledge; appreciating the hermeneutic circularity of shared understanding; and triggering those 'light bulb' moments. The importance of attending to different and at times conflicting perspectives is underscored.